2017
DOI: 10.7150/jca.16584
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prolonged exposure to low dose metformin in thyroid cancer cell lines

Abstract: Background: Thyroid cancer is generally associated with an excellent prognosis, but there is significant long-term morbidity with standard treatment. Some sub-types however have a poor prognosis. Metformin, an oral anti-diabetic drug is shown to have anti-cancer effects in several types of cancer (breast, lung and ovarian cancer). The proposed mechanisms include activation of the Adenosine Mono-phosphate-activated Protein Kinase (AMPK) pathway and inhibition of the mTOR pathway (which promotes growth and proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Besides, we suspected the fact, that the concentrations of metformin used in experimental studies were much higher than therapeutic human plasma concentrations [ 46 ], should be responsible for limiting the extrapolation of these findings to clinical practice. But a previous study demonstrated that even at low physiological doses (0.3-1 mM) exposure to metformin dampened proliferation, colony formation and migration, and the anti-proliferative effects [ 47 ]. In fact, although the inhibitory effects in most of laboratory studies were observed at concentrations which are at least 10-fold higher than the peak plasma concentration attained with typical dosing in diabetics, there are emerging studies which show that even very low doses of metformin could have substantial anti-cancerous effects [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, we suspected the fact, that the concentrations of metformin used in experimental studies were much higher than therapeutic human plasma concentrations [ 46 ], should be responsible for limiting the extrapolation of these findings to clinical practice. But a previous study demonstrated that even at low physiological doses (0.3-1 mM) exposure to metformin dampened proliferation, colony formation and migration, and the anti-proliferative effects [ 47 ]. In fact, although the inhibitory effects in most of laboratory studies were observed at concentrations which are at least 10-fold higher than the peak plasma concentration attained with typical dosing in diabetics, there are emerging studies which show that even very low doses of metformin could have substantial anti-cancerous effects [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study published in 2017 analyzed the growth inhibitory effects of metformin on a variety of thyroid cancer cell lines with different origins -FTC, PTC, ATC and MTC -and normal thyroid follicular cells. Irrespective of the origin of thyroid cancer cell lines, metformin suppressed cellular proliferation at concentrations that fall within the therapeutic range (Kheder et al 2017). In another study, the anti-cancer effects of metformin were tested in two MTC cell lines, TT and MZ-CRC-1.…”
Section: Preclinical Evidencementioning
confidence: 99%
“…Many preclinical studies [ 60 , 64 , 65 ] mentioned that metformin was related to cell growth inhibitory because of cell proliferation inhibition instead of induction of cell apoptosis or necrosis. This evidence indicated that patients who had monotherapy with metformin might not lead to complete remission of the carcinoma.…”
Section: Resultsmentioning
confidence: 99%